2013
DOI: 10.1155/2013/105912
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling of Particulates Erosive Effect on a Commercial Scale Pipeline Bend

Abstract: The computational fluid dynamics modeling of solid particles hydrodynamic based on the Lagrangian framework for diluted solid-gas flow through 90° gas pipeline bend is carried out to discover the effect of particles size distribution on particles flow pattern and their erosive effect on the bend. Particles size distribution has been obtained experimentally by measuring the sizes of solid particles that are flowing through the gas pipelines of Aghajari gas booster station. Also the erosion rate at the outer wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Therefore, the equation of motion can be simplified to the following form: where [ 27 ] wherein Re p is the particle Reynolds number and is given as [ 28 30 ] …”
Section: Governing Equations Of Turbulent Micro- and Nanofluids Ermentioning
confidence: 99%
“…Therefore, the equation of motion can be simplified to the following form: where [ 27 ] wherein Re p is the particle Reynolds number and is given as [ 28 30 ] …”
Section: Governing Equations Of Turbulent Micro- and Nanofluids Ermentioning
confidence: 99%
“…43–45 have integrated these conditions, as seen in the following equation where mp' corresponds to the particles' mass flow; G is a constant that depends on the size of the particles and their effects; K' is a constant that depends on the eroded material surface; v is the particle velocity; n is an experimental coefficient equal to 2.6 (the terms in the parenthesis describe the geometric conditions where the erosion process is taking place), ρt represents the eroded material density; Apipe is the pipeline transversal section area; C1 is a factor that depends on the geometry of the model under analysis, for elbows, normally it is equal to 2.5. It can also be observed that the mathematical model is restricted to be applied only on pipelines/elbows/bends, and once again, as previously described, even when authors have stated that they have validated these models, 4,16,18–30 such validations have been performed on pipelines of small diameters and to the date there is no work showing validation on pipelines with diameters greater than 3 in., with high pressure, high temperature, and high flow rate along with critical ambient conditions.…”
Section: Empirical Erosion Analysismentioning
confidence: 98%
“…As described above, for the case of experimental work, most the work done has been performed with pipes with relatively small diameter and the experimental set up has been built in a manner such that the operational conditions can be easily controlled. 4,18–30 However, the pipelines for the oil and gas industry and real operating conditions have larger diameters and additionally the hydrocarbons are transported at high flow pressures with sand particles of different diameters, consequently performing experimental work to analyze sand erosion in real pipeline operation conditions becomes very complicated. Mohyaldin et al.…”
Section: Introductionmentioning
confidence: 99%